Philosophy of Constitutional Law: Analysis of the Resolutions of the National Council of the Judgment, Today National Board of Justice (JNJ) - Zelada Flores, Jaime Alejandro (2022)
Social factors influence the evolution of Constitutional Law. However, the Philosophy of Constitutional Law, by making a rational study of the regulations, in a universal social context, proposes alternatives in the search for solutions. In this scenario, this research work is carried out, on “The Constitutional Court and the Interpretation of the Resolutions issued by the National Council of the Magistracy in matters of evaluation and ratification of magistrates” and analyzing the Resolutions of the National Council of the Magistrature, today JNJ, within a socio-legal context. In this regard, Article 142 of the 1993 Constitution, regulates that: “The resolutions of the National Elections Jury, in electoral matters, nor those of the National Council of the Magistracy in matters of evaluation and ratification of elections, are not reviewable in court. judges”. However, the Constitutional Court interpreted that the filing and declaration as founded of a claim for amparo against the CNM is feasible. In that sense and after carrying out the study of the sentences issued, on this particular, it is observed that the interpretation work carried out exceeds the limits of this Institution; constitutional reform being appropriate.